For Better or Forever: Formal versus Informal Enforcement - Sobel, Joel (Journal of Labor Economics, 2006)
This article contrasts supporting partnerships through relational contracting and supporting partnerships through formal legal institutions. A large population of players interact in bilateral relationships. Efficiency requires cooperation, but cheating yields a higher short‐term payoff. There is a positive probability that the maximum feasible payoff available to a partnership decreases. Opportunistic behavior makes it impossible to realize the efficient outcome. A legal system can lead to efficient contracting. Without such a system, productive relationships arise in equilibrium if it is costly to initiate new relationships. This type of relational contracting tends to make partnerships last longer than is efficient.